Synthesis and characterization of amino acids/hydroxyapatite composites for in vitro remi-neralization of acid-etched bovine enamel - LIU Ji-tao; CHUAN Ding-ze; YANG Ze-bin; CHEN Xi-liang; YAN Ting-ting; CHEN Qing-hua (Cailiao gongcheng, 2019)
Amino acids modified hydroxyapatite (AA/HAP) composites were synthesized in the presence of different concentrations of serine (Ser), aspartic acid (Asp) and glutamic acid (Glu). The composites were characterized by Fourier transform infrared spectrometer, X-ray diffractometer (XRD) and transmission electron microscope (TEM), and were evaluated in the in vitro remineralization of acid-etched bovine enamel. The results show that amino acids (AA)can interfere with the growth of HAP crystal plane, resulting in the increase of the solubility and decrease of the ordered structure of the HAP crystals. XRD patterns and TEM analysis show that AA has a significant inhibitory effect on the[100] crystalline direction of HAP.Meanwhile, the HAP composites modified by AA have refined crystalline size when compared with the HAP without AA. The cytotoxicity of the materials was evaluated by CCK-8 assay and the results show that the relative cell activity of AA/HAP composites is better than the HAP. Field emission scanning electron microscope images show that the HAP without amino acids and the HAP modified with two different concentrations of amino acids both can repair the surface lesions of bovine enamel. While only the AA/HAP synthesized in the presence of 10 mmol·L-1 Ser, Asp and Glu generates a dense remineralization layer with a thickness of approximately 22 μm in the subsurface restoration, and obtains the best surface microhardness recovering.